Case Report: Suspected “stiff dog syndrome” in a Maltese dog - Buffagni, Valentina; Fidanzio, Francesca; Dell’Apa, Diletta; Tummolo, Fabio; Bernardini, Marco; Bianchi, Ezio (Frontiers in Veterinary Science, 2025)
A Maltese dog was presented with a stiff gait, secondary to muscle hypertonicity, affecting the axial and proximal appendicular muscles, which had progressively worsened over the last 4 years, associated with episodes of muscle spasms. Neuroanatomical localization was upper motor neuron (UMN) or generalized neuromuscular system. Cerebrospinal fluid (CSF) analysis was normal. Magnetic resonance imaging (MRI) of the brain and cervical spinal cord was performed and showed hypoplasia of the dorsal part of the left hippocampus, unchanged compared to the MRI performed 4 years earlier, and mild C6–C7 disk extrusion, with no evidence of compression of the spinal cord. Conscious electromyography showed continuous motor unit action potentials (MUAPs) in agonist and antagonist muscles. Indirect immunofluorescence (IFT) detected the presence of antibodies against glutamic acid decarboxylase (GAD). These findings were consistent with a human condition called “Stiff Person Syndrome” (SPS). A condition similar to SPS has only been described once before in a Beagle dog (“Stiff Dog Syndrome”). A therapeutic protocol based on human guidelines for SPS was initiated with a partial improvement. “Stiff Dog Syndrome” (SDS) is a possible cause of muscle hypertonicity and spasms in dogs.